Electron spin resonance study of light-induced conformational changes in nitroxide labelled bovine rhodopsin. - Rowntree, J; Watts, A (1988)
Bovine rhodopsin was isolated in the unbleached form as a retinal disc membrane suspension and spin-labelled with 4-maleimido-2,2,6,6-tetramethylpiperidine-N-oxyl. Both conventional and saturation transfer electron spin resonance methods were used to investigate the sensitivity of the spin-label to conformational changes of rhodopsin induced by both transient and long-term exposure to light. The results indicate that the ESR methods do display sensitivity to such changes. An exponential decay curve with a time constant of 10 s was obtained by following the height of a single peak in the saturation transfer electron spin resonance spectrum in response to a single light flash.